Modernisasi Pengelolaan Keuangan dan Produk Bank Sampah - Evy Rahman Utami; Arum Indrasari; Sri Budhi Rezki (Universitas Muhammadiyah Surabaya, 2019)
Waste bank is one of alternatives to solve waste problem in a community. Cahaya Baru waste bank is in Kruwet hamlet, Sumberagung village, Moyudan sub-district, Sleman district, Yogyakarta Special Region province. There are two main problems faced by the partner in managing waste bank, which are the waste managers who have not been able to prepare financial statement of the waste bank and the community has not had the willingness and skills to utilize the garbage into economic goods, especially non-organic waste. In accordance with waste bank financial statement, this community service held trainings on preparing waste bank financial statement and waste saving book. Besides that, this activity also conducted counseling on the importance of overcoming household waste and training in making various kinds of handicrafts from waste materials into economic goods. The counseling and trainings were able to make people aware of waste management and waste managers could prepare financial statements manually and have waste saving provided for customers. Based on this program, the managers were able to record selling report from January to Mei 2018 period for 1,812,842 IDR with the customers achieving 20% of all household heads in Kruwet hamlet.